Safety and efficacy of intracardiac echocardiography-guided zero-fluoroscopy ablation in atrial fibrillation patients: a comparative study of high-power short-duration and low-power long-duration strategies - Liu, Guang-an; Shao, Bo; Wu, Wanglong; Zhou, Linxiao; Cui, Jing; Chen, Wenxue; Zhang, Ruoxi; Liu, Feng (Frontiers in Cardiovascular Medicine, 2024)
IntroductionIn atrial fibrillation (AF) ablation, fluoroscopy has been a standard tool for catheter guidance. However, the combination of electroanatomic mapping systems (EAMs) and intracardiac echocardiography (ICE) now allows for minimal or zero-fluoroscopy procedures. Concurrently, high-power short-duration (HPSD) ablation has emerged as a promising technique, offering enhanced resistive heating while reducing conductive heating. This approach potentially improves both safety and efficacy. Despite these advancements, there is a lack of comprehensive clinical data on the safety and effectiveness of HPSD ablation when used in conjunction with ICE-guided zero-fluoroscopy procedures.ObjectiveTo compare two different ablation strategies—high-power short-duration (HPSD) and low-power long-duration (LPLD)—both utilizing intracardiac echocardiography (ICE)-guided zero-fluoroscopy in the context of atrial fibrillation (AF) ablation.MethodsThis retrospective study included 173 consecutive patients with AF who underwent ICE-guided zero-fluoroscopy ablation. Patients were divided into two groups: HPSD and LPLD. All procedures were conducted using an EAM system with ICE guidance. Both groups underwent routine pulmonary vein isolation (PVI), with additional linear ablations performed for persistent AF when necessary. We compared treatment outcomes and the incidence of complications between the two groups.ResultsAll procedures were successfully completed under ICE-guided zero-fluoroscopy, establishing a feasible and reliable workflow. The procedure and ablation times were significantly shorter in the HPSD group compared to the LPLD group. At one-year follow-up, sinus rhythm was maintained in 77 patients in the HPSD group and 74 patients in the LPLD group, with no significant difference between the two group. Postoperative complications occurred in 5 patients in the HPSD group and 3 patients in the LPLD group. Importantly, there were no major adverse cardiac and cerebrovascular events (MACCE) in either group.ConclusionA zero-fluoroscopy workflow utilizing an EAM system combined with ICE appears to be both feasible and safe for ablation in AF patients. In patients undergoing ICE-guided zero-fluoroscopy ablation, the HPSD strategy is comparable to LPLD ablation in effectiveness while offering the benefit of shorter procedure and ablation times.